Maximum power point tracking architectures for photovoltaic systems in mismatching conditions: a review. Issue 6 (1st June 2014) - Bastidas‐Rodriguez, Juan David; Franco, Edinson; Petrone, Giovanni; Ramos‐Paja, Carlos Andrés; Spagnuolo, Giovanni
Abstract : In practical photovoltaic (PV) installations the operating conditions of the panels the PV array is made of are different owing to different factors. Such irregular conditions are known as 'mismatching conditions' and produce multiple maxima in the power‐voltage curves of any PV array. The traditional maximum power point tracking (MPPT) techniques are able to track one of those maxima, but they cannot guarantee the extraction of the maximum power the PV array would be able to deliver. To overcome this problem, many techniques have been presented in the literature: they use one converter for the entire array (centralised MPPT), one converter for each part of the array (distributed MPPT) or they reconfigure the PV array (RMPPT). This paper presents the general architectures used by 61 different MPPT techniques, by discussing their main advantages and disadvantages, in order to give to the reader a comprehensive view of both the control strategies and the architectures for extracting the maximum power from a mismatched PV field. Moreover, the widely adopted techniques for each hardware structure are presented in a structured and compact way, thus providing to the reader some guidelines regarding the technique's operation principle and hardware requirements.